Intercourse as Interaction in Economics - Nikova, Donka (Research Papers, 2016)
This work presents a theoretical research of the interaction as a form of the intercourse in economics.Objective of the research: to to clarify the essence and the structural characteristics of the intercourse in economic activity with a main goal: to enhance the scientific and practical-applied explicitness of the economics.Object of the research: the economic activity of people.Subject of the research: the intercourse as interaction in the economics.Thesis of the research: the intercourse in the economics is impossible without the interaction as its main form.Method of the research: the method of theoretical analysis, realized under the frame of the psychological theoretical approach.Results of the research: the adoption of the statement that the enhancement of the economic activity’s effectiveness is related to the successful intercourse as interaction in the economics. The enhancement and the development of the successful interaction as a form of the intercourse in economic activity will most likely enhance the economics.The results of the research have their practical and theoretical significance.